(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2023)
As we know, Great Britain is one of the developed countries in Europe. It includes the sovereign states of England, Wales, Scotland and Northern Ireland. In this article, we will talk about this country in detail. We provide valuable information about the British government and its important historical dates.